Paraduodenal Pancreatitis Imaging and Pathologic Correlation of 47 Cases Elucidates Distinct Subtypes and the Factors Involved in its Etiopathogenesis - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2017)
Clinicopathologic characteristics of paraduodenal (groove) pancreatitis (PDP) remain to be fully unraveled. In this study, 47 PDPs with preoperative enhanced images available were subjected to detailed comparative analysis in conjunction with pathologic findings. PDP were predominantly in males (3: 1) with a mean age of 50 years, and 60% had a preoperative diagnosis of cancer. Mean lesional size was 3.1 cm. Three distinct subtypes were identified by imaging. Solid-tumoral (type-1) with groove-predominant (type-1A, 36%) forming a distinct solid band between the duodenum and pancreas often with histologic microabscesses (69% vs. 33% in others), and pancreas-involving (type-1B, 19%) forming a pseudotumoral mass spanning into the head-groove area, always diagnosed preoperatively as cancer, but often lacked parenchymal atrophy of the body (44% vs. 92%). Cyst-forming (type-2) had groove-predominant (type-2A, 15%), often accompanied by Brunner gland hyperplasia, and pancreas-predominant (type-2B, 15%) were in younger (mean: 44 y) females (57% vs. 18%) and had less alcohol/tobacco abuse (50/33% vs. 81/69%). Ill-defined (type-3; 15%) often had main pancreatic duct dilatation (mean: 5.6 vs. 2.8mm). The capricious presentations of PDP could be attributed to variable effects of different mechanistic and precipitative etiopathogenetic factors such as disturbed accessory duct outflow (dilated Santorini duct, 87%), aggravated by alcohol (77%) with superimposed stasis in the main ampulla (previous cholecystectomy, 47%; choledocholithiasis, 9%), strictured Wirsung duct (68%), and some likely exacerbated by ischemia (hypertension [59%], tobacco abuse [64%], arteriosclerosis in the tissue [23%]). In conclusion, our study identified 3 distinct types of PDP and each may reflect different pathogenetic contributing factors.
Keywords: paraduodenal; groove; IgG4; pancreatic cancer; autoimmune pancreatitis; pancreatitis; classification; pathogenesis; GEL; LPSP; COMMON BILE-DUCT; GROOVE PANCREATITIS; DUODENAL WALL; DIAGNOSTIC CHALLENGE; HETEROTOPIC PANCREAS; CYSTIC DYSTROPHY; FEATURES; CANCER; RISK; MRI